Parâmetros populacionais de peixes oportunistas da planície de inundação do alto rio Paraná : influências do El Niño Southern Oscillation - ENSO. - Silva, Willian Eduardo Ferreira da (2022)
The occurrences of El Niño - Southern Oscillation – ENSO climate events promote alterations in the global hydrological cycle, so that the precipitation pattern results in periods of extreme drought and floods in certain continental regions. The irregularity of rainfall inconstantly changes the hydrometric level of aquatic bodies, the flood pulse and the river discharge, which in turn alter the limnological variables, the primary productivity and the availability of resources and habitat for the aquatic organisms, possibly affecting their growth and reproduction patterns. Therefore, the population parameters (such as sex ratio, size at first sexual maturity, weight-length ratio and somatic growth) of the short-lived icthyofauna (CVC) in the upper Paraná River floodplain (PIARP) were evaluated and compared in different climate periods (El Niño, La Niña and Neutral) through statistical modeling, under Bayesian perspective. The population parameters were estimated for the Hyphessobrycon eques species, for it was one of the selected species that presented traits of opportunistic strategy, being so characterized as a short life cycle species. The results found partially corroborated with the predictions, that the highest sex ratio found was for the La Niña period (2.7 females for one male), followed by Neutral (2.3) and El Niño (1.3) periods. For the first maturity sizes (L50), estimated for both sexes, they were smaller in the La Niña period (23.87mm for females and 23.35mm for males), followed by the El Niño period (25.89 mm for females and 28.75mm for males) and Neutral period (25.97mm females/ 29.92mm males). The weight-length ratio showed that the male body shape (α) had a slightly higher body biomass (α) average than females in the Neutral and La Niña periods. However, in the El Niño period, the opposite of the other periods was observed. The estimated parameters for the female body shape (α) were higher in Neutral, followed, respectively, by the El Niño and La Niña period, though, for males, the body shape (α) was higher in Neutral, followed by the La Niña and El Niño period. The estimated median lengths for the ages are moderately longer in males than females. Furthermore, the estimated median lengths are relatively longer in extreme periods (La Niña and El Niño) for the initial ages (3 and 6 months) when compared to the Neutral period, both for males or females. For females, the estimated median lengths are comparably longer in the El Niño period than in the La Niña period, while the opposite is observed for males. For that reason, the reproductive tactics of H. eques presented in the La Niña period can be a population level’s response, used for the optimization of the reproductive success and for the maintenance of the species in the environment.